A comunicação organizacional como processo estratégico de fortalecimento dos pequenos negócios: O desenvolvimento de uma plataforma de comunicação para as pequenas empresas de São Luís/MA. - SETUBAL, Gleicilene Pereira (2022)
From the positive impacts that communication has on organizations, this dissertation consists of research applied to the organizational context of small businesses in Ludovicenses, which aims to discuss the possibilities of communication as a strengthening process for small businesses. In the first instance, using a bibliographic survey, it makes a brief conceptual review of the concept and evolution of communication, bringing some insights into the new perspectives of its performance in the context of small organizations, starting from the idea that when thinking about organizational communication in the In the context of small organizations, it is observed that there is a need to break with the paradigms that constrain organizational routines and are impeding factors for development. In this way, taking into account the structural and communicational particularities of small businesses in São Luís (MA), it is proposed as a product of this research, the development of a digital content platform, better known as "content hub", a space where -line capable of being a source of information and a space for interactions on various fronts of organizational communication, as well as capacity building and training for local entrepreneurs. The methodological process of creating the product was guided by the Design Thinking methodology, which is premised on empathy in the development of projects, in line with the concepts for the development of web pages and digital communication products. When used by small organizations, the objective of the platform is to allow access to concepts and practices of organizational communication, events and training while building a network of knowledge exchange between these entrepreneurs. Over time, it is believed that this tool tends to contribute to the creation of an entrepreneurial community that is more alert and prepared for the dynamics of organizational communication in their businesses.